Course registration via interactive mobile phone application / Nor Asida Mohd Hanapiah - Mohd Hanapiah, Nor Asida (2005)
From the questionnaires several problems were found out usually faced every semester by Faculty of Information Technology and Quantitative Sciences (FTMSK) students while using pc-based online course registration. Initially developed to help minimising paper works and make it easier for students to register subjects, these problems highlight the needs of finding alternative registration method. Due to its mobility and affordability, mobile phone is seen as the viable alternative platform to replace pc-based online course registration. As such, in this project, a mobile phone application based on JAVA language was developed. This application offers similar functions as the online system such as add and delete subject but with simpler methods. Hopefully with this application, the problems faced by student previously can be eliminated while at the same time maximising the potential of mobile phone technology in daily student life.